2007
DOI: 10.1080/07328300701298196
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis ofO‐β‐D‐Glucopyranosides of 7‐Hydroxy‐3‐(imidazol‐2‐yl)‐4H‐chromen‐4‐ones

Abstract: The 7-hydroxy-3-formyl-4H-chromen-4-one 1 reacted with various cyclic 1,2-dicarbonyl compounds in the presence of ammonium acetate to furnish 7-hydroxy-3-([4,5-fused] imidazol-2-yl)-4H-chromen-4-ones 2a-f, which on glucosylation with a-acetobromoglucose affords 2,3,4,6-tetra-O-acetyl-b-D-glucopyranosyloxy-3-([4,5-fused] imidazol-2-yl)-4H-chromen-4-ones 3a -f. 7-O-b-D-Glucopyranosyloxy-3-([4,5-fused] imidazol-2-yl)-4H-chromen-4-ones 4a -f were prepared by deacetylation with anhydrous zinc acetate in absolute me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Glucosylation of 2-(4-hydroxyphenyl)-4,5-disubstituted imidazoles with acetobromoglucose (ACBG) followed by deacetylation leads the desired O-glucoside FT-IR data of the O-glucoside are in agreement with the assigned structure. Anomeric configuration confirmed by 1 H NMR since the coupling constant of the compound 8.5 Hz was observed between H-1 and H-2 proton. 13 C NMR spectrum, C-1 resonated downfield of the other glucosyl carbon at d 100.26 consistent with the formation of O-bglucosides.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Glucosylation of 2-(4-hydroxyphenyl)-4,5-disubstituted imidazoles with acetobromoglucose (ACBG) followed by deacetylation leads the desired O-glucoside FT-IR data of the O-glucoside are in agreement with the assigned structure. Anomeric configuration confirmed by 1 H NMR since the coupling constant of the compound 8.5 Hz was observed between H-1 and H-2 proton. 13 C NMR spectrum, C-1 resonated downfield of the other glucosyl carbon at d 100.26 consistent with the formation of O-bglucosides.…”
Section: Resultssupporting
confidence: 55%
“…In continuation of our work [1] with imidazole ring which were very important in living systems like vitamin B 12 . Imidazole also forms a part of some important compounds such as purine, adenine, xanthine, guanine, co-enzyme-a.…”
Section: Introductionmentioning
confidence: 99%
“…56,57 The role of 1,2-dicarbonyl compound could be played by o-quinones (1,2-naphthoquinone, 9,10-phenanthrenequinone, and substituted isatines) (Scheme 16). 64 The synthesized compounds 43 and 44 were evaluated for their antimicrobial, antifungal, and antioxidant activities. It was shown that glucosidated derivatives 44 are more active than their analogs 43 unsubstituted at the position 7 of the chromone ring.…”
Section: (See Scheme 8)mentioning
confidence: 99%
“…So, continuation of our work [32][33][34][35][36][37][38] and keeping view of the various biological activities, it was proposed to synthesize new molecules containing thiazole, azomethine, O-glucoside, and sulfonamide moiety in one frame-work.…”
Section: Introductionmentioning
confidence: 99%